Selection of low impact development technical measures in the distribution area of expansive soil: a case study of Hefei, China - Huang, Ming; Liu, Zhen; Zhang, Rui; Tao, Yong; Sun, Ya-min (Frontiers in Environmental Science, 2024)
Expansive soils are widely distributed around the world. They have significant characteristics of both hygroscopic expansion and water-loss shrinkage, which have caused serious damage to road paving, construction of low-rise houses, and construction of slopes along the banks of rivers. Similarly, the implementation of low impact development measures can cause considerable difficulties in the distribution area of expansive soil. The entire urban area of Hefei is situated on expansive soil. Although Hefei city has developed a sponge city plan, it has not been carried out on a large scale for implementation of low impact development technical measures. Experimental studies have shown that exposed expansive soils produce fissures that run up and down during wet and dry cycles. These fissures are extremely unfavorable to the infiltration of surface runoff formed by short-term heavy rainfall. This is also one of the reasons for short-term rainfall in Hefei city, resulting in serious flooding in low-lying areas with a poor drainage system. At the same time, initial rainfall is ineffective in cleaning up surface source pollution. Therefore, we can enhance the characteristics of expansive soil, keep the expansive soil unexposed, and maintain a certain level of humidity. These approaches can play a better role in the control of rainfall runoff and surface source pollution. The characteristics of expansive soils can be enhanced by mixing them with weathered sand, a physical improvement, to meet the technical requirements for infiltration, interception, and purification. It is recommended to carefully select low impact development measures in the distribution area of expansive soil to avoid the occurrence of wasteful investment and poor results.